Magneto-photoconductivity of three dimensional topological insulator bismuth telluride - Cao, Bingchen (2018)
Magnetic field dependence of the photocurrent in a 3D topological insulator is studied. Among the 3D topological insulators bismuth telluride has unique hexagonal warping and spin texture which has been studied by photoemission, scanning tunnelling microscopy and transport. Here, we report on low temperature magneto-photoconductivity, up to 7 T, of two metallic bismuth telluride topological insulator samples with 68 and 110 nm thicknesses excited by 2.33 eV photon energy along the magnetic field perpendicular to the sample plane. At 4 K, both samples exhibit negative magneto-photoconductance below 4 T, which is as a result of weak-antilocalization of Dirac fermions similar to the previous observations in electrical transport. However the thinner sample shows positive magneto-photoconductance above 4 T. This can be attributed to the coupling of surface states. On the other hand, the thicker sample shows no positive magneto-photoconductance up to 7 T since there is only one surface state at play. By fitting the magneto-photoconductivity data of the thicker sample to the localization formula, we obtain weak antilocalization behaviour at 4, 10, and 20 K, as expected; however, weak localization behaviour at 30 K, which is a sign of surface states masked by bulk states. Also, from the temperature dependence of phase coherence length bulk carrier-carrier interaction is identified separately from the surface states. Therefore, it is possible to distinguish surface states by magneto-photoconductivity at low temperature, even in metallic samples.